Characteristics of Jelly Fungus (Tremella fuciformis, Berk.) As an Edible Mushroom - Jumhawan Ratman Permana; Awan Purnawan (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Jelly fungus (Tremella fuciformis, Berk.) belongs to the basidiomicetes familyor auricularia  familyand into the white fungus species. As an edible mushroom called jelly mushroom, snow fungus, silver mushroom or white jelly it can be made for the basic ingredients of juice drinks, ice cream and porridge mixor soup in addition to efficacy as a medicine and serves as a supplement. Characteristics of fruiting bodies of this fungus in wet water content showed gelatinous (chewy), smooth, elastic, but a conversely it will turn into rigid with curved in a dry state. The fruiting body of T. fuciformis, Berk. Had was isolated from  trembesi wood cross section (Samanea saman, Jacq. Merr.) found around of the Tajur village in Bogor city. The purpose of this study was to determine more closely the growth characteristics of the fruiting bodies by isolating then on solid medium potato dextrose agar (PDA) by the incubation temperature at 15oC. During the incubation period within 3 months there was  no growth of mycelium showen, but  the viability of the growth of the fruiting  body appeared to be still fresh. The fungal growth on a wood as a medium of fungal fruiting bodies naturally produce as much as 375 grams in the harvest period during the next three months. However there will be no fruiting bodies produced afterwards. The cultivation of T. fuciformis, Berk. commercially can be done in sawdust medium in the plastics bag (baglog).